2019
DOI: 10.1371/journal.pone.0220770
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the soil microbiome and quantifying antibiotic resistance gene dynamics in agricultural soil following swine CAFO manure application

Abstract: As agriculture industrializes, concentrated animal feeding operations (CAFOs) are becoming more common. Feces from CAFOs is often used as fertilizer on fields. However, little is known about the effects manure has on the soil microbiome, which is an important aspect of soil health and fertility. In addition, due to the subtherapeutic levels of antibiotics necessary to keep the animals healthy, CAFO manure has elevated levels of antibiotic resistant bacteria. Using 16s rRNA high-throughput sequencing and qPCR, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
28
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 94 publications
6
28
1
Order By: Relevance
“…We compared the abundance of intI1, sul1 and tetG in the goat bedding and goat pellet samples with the literature, expecting our results would have a lower prevalence of ARGs compared to reported quantities of ARGs in conventional farms, also known as concentrated animal feeding operations (CAFOs). Instead, we found that our results were on the same order of magnitude of 10 -3 gene copies per 16S rRNA gene for intI1 and tetG in pellets, and a greater order of magnitude for sul1 (Lopatto et al, 2019;Cheng et al, 2013). Since our samples were not actively influenced by antibiotics, but have comparable values to many studies that did use soil influenced by antibiotics, this raises the question of whether antibiotic usage promotes ARGs in microbial populations.…”
Section: Discussioncontrasting
confidence: 47%
“…We compared the abundance of intI1, sul1 and tetG in the goat bedding and goat pellet samples with the literature, expecting our results would have a lower prevalence of ARGs compared to reported quantities of ARGs in conventional farms, also known as concentrated animal feeding operations (CAFOs). Instead, we found that our results were on the same order of magnitude of 10 -3 gene copies per 16S rRNA gene for intI1 and tetG in pellets, and a greater order of magnitude for sul1 (Lopatto et al, 2019;Cheng et al, 2013). Since our samples were not actively influenced by antibiotics, but have comparable values to many studies that did use soil influenced by antibiotics, this raises the question of whether antibiotic usage promotes ARGs in microbial populations.…”
Section: Discussioncontrasting
confidence: 47%
“…Further microbial community analyses are needed to connect microbial community diversity and ARG attenuation or proliferation, and deeper taxonomic analysis than the genera level may provide insight to potential pathogenicity which will allow for bacterial host identification across the preharvest vegetable production chain. Other studies have indicated need to examine this more closely specifically in agricultural soils (Cycoń et al, 2019;Lopatto et al, 2019) and on vegetable surfaces Shen et al, 2021).…”
Section: Pre-harvest Conditions On Taxonomic Compositionmentioning
confidence: 99%
“…The microbial populations associated with manure varies due to numerous influential factors, including the producing animal, its feeding regime and the waste management practices (Albihn and Vinnerås, 2007;van Vliet et al, 2007;Jokinen et al, 2012;Lopatto et al, 2019). Manure application can inadvertently spread zoonotic diseases to humans while both animal and plant populations can also be vulnerable to disease (Albihn and Vinnerås, 2007;Spiehs and Goyal, 2007;Longhurst et al, 2019;Tran et al, 2020).…”
Section: Bacteria Manure and Soilmentioning
confidence: 99%